CARACTERIZAÇÃO DE PACIENTES COM INDICAÇÃO CLINÍCA PARA CARIÓTIPO EM UM HOSPITAL DE REABILITAÇÃO. - Carvalho, Antonio Alberto (2006)
In this study the results of the evaluation cytogenetics of 694 patients with suspected of being carriers of chromosomal abnormality, seen in Sarah Network of Hospitals for Rehabilitation - San Luis Unit, in the period from December 1996 to January 2005.